2014
DOI: 10.1016/j.jse.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Rat rotator cuff tendon-to-bone healing properties are adversely affected by hypercholesterolemia

Abstract: Background Rotator cuff tendon tears represent a major component of reported orthopaedic injuries. In addition, more than one quarter of U.S. adults either currently have high cholesterol levels or have reduced their previously high cholesterol levels through the use of pharmaceuticals. Our clinical data have already linked hypercholesterolemia to full-thickness rotator cuff tears, and experimental data from our laboratory have shown effects on native tendon properties in multiple species. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 16 publications
4
66
0
Order By: Relevance
“…In mice, chronic hypercholesterolemia decreased the elastic modulus of patellar tendons, which can increase the susceptibility of tendons to rupture 3 . For rats that received a rotator cuff tear and repair, a high cholesterol diet was associated with decreased healing stiffness one month after repair 4 . While Abboud and colleagues did not directly explore statins in their studies, they postulated that these medications may have a positive impact on tendon-bone healing.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In mice, chronic hypercholesterolemia decreased the elastic modulus of patellar tendons, which can increase the susceptibility of tendons to rupture 3 . For rats that received a rotator cuff tear and repair, a high cholesterol diet was associated with decreased healing stiffness one month after repair 4 . While Abboud and colleagues did not directly explore statins in their studies, they postulated that these medications may have a positive impact on tendon-bone healing.…”
Section: Discussionmentioning
confidence: 95%
“…These medications are most commonly used in the treatment of hypercholesterolemia, as they are very effective at lowering low-density lipoprotein cholesterol and improving clinical outcomes of patients with coronary artery disease and other cardiovascular conditions 6; 31 . In addition to promoting cardiovascular disease, hypercholesterolemia is associated with a greater risk for rotator cuff tendon tear and impaired tendon-bone regeneration 1; 4 . Aside from their efficacy in treating hypercholesterolemia, there are emerging roles for statins in the treatment of inflammatory diseases 6; 31 .…”
Section: Introductionmentioning
confidence: 99%
“…This data would support hypercholesterolemia likely plays a role not only in the development of rotator cuff tearing but also on the ability for a tendon to heal after repair. Similarly, diabetes has been found to have a detrimental effect on tendon healing using a rat rotator cuff tear model [39] . Modification of serum cholesterol levels and blood glucose levels may play a role in improving healing after repairs.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
“…Consequently, patients with cuff tears are more likely to have hypercholesterolemia compared to controls. Beason et al [39] evaluated the effects of hypercholesterolemia on tendon healing in a rat rotator cuff tear model. These authors determined that there was a significant reduction in rotator cuff repair stiffness in hypercholesterolemic rats compared with controls [40] .…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
“…Rabbits with elevated cholesterol had significantly different mechanical tendon properties, with lower load-to-failure and diminished elasticity, and increased tendon fat-to-muscle ratio compared with the control groups (p<0.05) 13. Beason et al 12 identified statistically significant abnormalities in tendon stiffness in high-cholesterol rats versus control rats at the short-term, 4-week mark. This relationship disappeared at the 8-week mark, and no significant histological differences in the rotator cuff tendons at the 8-week mark were identified.…”
Section: Discussionmentioning
confidence: 99%